2022
DOI: 10.1177/00315125211073404
|View full text |Cite
|
Sign up to set email alerts
|

Practical Applications for Designing Soccer’ Training Tasks From Multivariate Data Analysis: A Systematic Review Emphasizing Tactical Training

Abstract: Novel viewpoints have led to an understanding that good soccer performers are capable of continuous decision-making and performing excellent motor skills in a well conditioned mental state. Our aims in this review were to: (a) summarize the effects of different conditions and constraints on a soccer player’s response and (b) identify potential training designs for varied soccer tasks from a multivariate perspective, emphasizing tactical training. We performed a systematic literature review according to PRISMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…What seems to be a consensus is that, in the context of soccer training, finding the most appropriate formatting can promote in players an adaptation that favors affordances (opportunities to act) in various situations within the task ( Rico-González et al, 2022 ). In this sense, and more focused on providing an environment that enhances creative actions, the present study sought a calculation of the relative area per player (calculated as the field area divided by the number of players involved in the game), as variations in this relative space can change athletes’ responses ( Clemente et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…What seems to be a consensus is that, in the context of soccer training, finding the most appropriate formatting can promote in players an adaptation that favors affordances (opportunities to act) in various situations within the task ( Rico-González et al, 2022 ). In this sense, and more focused on providing an environment that enhances creative actions, the present study sought a calculation of the relative area per player (calculated as the field area divided by the number of players involved in the game), as variations in this relative space can change athletes’ responses ( Clemente et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, small-sided games have been suggested as an appropriate and relevant training tool, as they allow for concomitant development of players' technical, physical, and tactical aspects of play [16,17]. In addition, coaches can vary the boundary conditions during these game-based scenarios to emphasise specific behaviours [18].…”
Section: Introductionmentioning
confidence: 99%
“…Player performance is dependent on the tactical abilities and cognitive processes underlying decision making [ 22 , 23 ]. Indeed, previous studies have reported an association between tactical performance, specific motor skills, perceptual–cognitive–motor skills, and decision making effectiveness in athletic development [ 24 , 25 , 26 ]. Specifically, the small-sided games (SSGs) have contextual dynamics that improve individual and collective technical–tactical expertise in young football players [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%